Development of Islamic Counseling Models To Improve Student’s Discipline - Edison Edison (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
The purpose of this study is to find out (1) the analysis of the needs of the Islamic counseling model. (2) Developing an Islamic counseling model to improve student discipline. This study uses a modified Borg & Gall model of research and development (R&D) methods, with data collection techniques through interviews and student discipline questionnaires. The results of this study indicate that (1) SMA Negeri 8 Makassar students based on observations and interviews with counselors, the Islamic counseling model to improve student discipline is urgently needed in schools. (2) Producing an Islamic counseling model as guidance for counseling services for counselors to improve student discipline that is useful, decent, appropriate, and acceptable material for students in SMA Negeri 8 Makassar.Â